Effect Of Panchgavya Ghrita On Fallopian Tube Blockage: A Single Case Report - kumari, Suman; Sharma, Sushila; Dave, Hetal H; Sonu (International Research Journal of Ayurveda & Yoga, 2020)
The present case study was carried out to evaluate the role of Uttar Basti in tubal blockage, in order to establish it as a safer and cost-effective Ayurvedic treatment modality. The criterion for selection of the patient is based on tubal blockage diagnosed in hysterosalpingography (HSG). Tubal blockage is responsible for 25 − 35% of female infertility. A female patient of 30 year old was presented with complaints of inability to conceive after 5 year of unprotected sex with involvement of tubal factor. Patient had bilateral tubal block in H.S.G. report. Patient was treated for tubal factor along with Panchagavya Ghrita Uttar Basti. Panchagavya Ghrita was selected for its Vata Kapha Shamaka and lekhana properties. The dose of Uttar Basti was 5 ml with duration of three consecutive cycles (three days of Uttar Basti in each cycle). Uttar Basti was administered, after cessation of menstruation, to the screened patient, through hematological, urinary and serological (CBC, HIV, VDRL, HBsAg) investigations. Three cycle of Uttar Basti (intra uterine) with Panchagavya Ghrita gave result that left fallopian tube was patent in H.S.G., while minimal spillage is seen in right fallopian tube in H.S.G.